Pengaruh Pendidikan Ibu Terhadap Kejadian Stunting pada Anak di Desa Lhok Setuy Kecamatan Baktiya Kabupaten Aceh Utara - Noeroel Arham; Ananda Alfinura (Universitas Muhammadiyah Manado, 2025)
This study aims to explore the influence of maternal education on the incidence of stunting in children in Lhok Setuy Village, Baktiya District, North Aceh Regency. Stunting is a chronic nutritional condition characterized by a child's height below the standard for their age, which is often caused by inadequate diet, poor sanitation, and limited access to clean water. Qualitative research methods were used involving eight mothers as respondents. Data were obtained through in-depth interviews and field observations to explore mothers' knowledge of child health, diet, access to sanitation facilities, and nutrition education. The results showed that most mothers in Lhok Setuy Village had adequate knowledge of the importance of exclusive breastfeeding, but only a small number were able to provide animal protein sources to their children. Most mothers also had healthy latrines at home, and access to clean water was not a major problem. Although mothers' knowledge of nutrition and child health was quite good, the application in everyday life still needs to be improved. These findings indicate that further support is needed in more specific nutrition and health counseling to help mothers in this village provide optimal nutrition for their children. Through more intensive educational interventions, it is hoped that the incidence of stunting can be reduced, so that the quality of life of children in Lhok Setuy Village can improve significantly.